Service Quality Analysis at Carwash 99 Garage - Muhammad Feziv Firdaus; Moh. Agung Surianto (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Carwash 99 Garage, which was established in 2016, is a rapidly growing car wash business in the automotive service sector, with the aim of meeting consumer demands for quality service. Despite many competitors, Carwash 99 Garage is able to face challenges and take advantage of opportunities to stay ahead. This study uses a qualitative method, which focuses on understanding phenomena related to behavior, perception, and action in a natural context, involving 4 informants: the owner, employees, and 2 customers. The results of the study indicate that Carwash 99 Garage has met various indicators of service quality. In the tangibles indicator, Carwash 99 ensures modern washing equipment and maintained cleanliness. For reliability, this business provides maximum work that makes customers satisfied. In the responsiveness indicator, employees are responsive and fast in providing services. In the assurance indicator, employees are always polite and provide the best service. Finally, in the empathy indicator, Carwash 99 Garage always tries to understand and fulfill the desires and needs of customers. Thus, Carwash 99 Garage has succeeded in providing services that satisfy customers and maintain their trust.